S-TYPE GRANITIC ROCKS OF PILAR DO SUL STOCK, SOUTHEAST OF THE SÃO PAULO STATE - Faria, Leandro Guerra [UNESP] (2024)
The Neoproterozoic granitic rocks of the Pilar do Sul Stock outcrop in the municipality of Pilar do Sul, southeast region of the São Paulo state, and are related to the magmatism evolution of the Agudos Grandes Granitic Batholith, linked to the Cotia Block, of the Apiaí Terrain. It is a body with 35 km2 and an elongated shape according to the general NE-SW direction, imposed by the Taxaquara Shear Zone deformation and intrusive in rocks of the metavolcanic-sedimentary sequence of the Votuverava Group of the Açunguí Supergroup. The rocks are represented by varieties of sieno-to monzogranite, predominantly isotropic to locally anisotropic, with light pink and light gray color, dominating the equigranular to inequigranular types of medium to coarse graining and rarely the porphyritic types. The hololeucocratic types predominate with the presence of aluminous minerals such as biotite, muscovite, rare garnet and tourmaline. They are rocks with contents above 71% of SiO2, high percentages of Al2O3 and K2O and negative anomalies of Rb, Ba, K and Sr, as well as negative anomalies of P, Zr, Ti, high values of Th and U, enriched in light rare earth elements in relation to heavy ones and negative anomalies of europium. They are high-potassium peraluminous leucogranites associated with a post-collisional environment of continental magmatic arc, with a signature of two micas granite type S, generated by the partial crustal fusion of metasedimentary rocks at deep crustal levels, associated to transtensive structures of the shear zones of the end stabilization of the Apiaí Terrain at the collisional event of the Ribeira Orogenesis.